2017
DOI: 10.21548/38-2-2330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Inoculation Regimes of Torulaspora delbrueckii and Oenococcus oeni on Fermentation Kinetics and Chemical Constituents of Durian Wine

Abstract: This work evaluated the effects of inoculation time of Oenococcus oeni on the kinetics of fermentation and chemical constituents of durian wine produced using a non-Saccharomyces yeast, Torulaspora delbrueckii. The growth of T. delbrueckii in mixed-culture fermentations was significantly adversely affected by the presence of O. oeni, and the growth of malolactic bacteria was also affected by the metabolism of yeast during fermentation. The level of ethanol produced in simultaneous alcoholic and malolactic ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
3
3
0
Order By: Relevance
“…This indicated that, although yeast died early, the ethanol likely inhibited the LAB, supported by the different ethanol levels and different LAB counts in co- and sequential fermentation. The results agreed with a previous study [ 10 ], where the highest cell population of LAB in mixed inoculation was also similar to that of LAB mono-inoculation. In addition, the decline of LAB may also be due to the lack of nutrients or the accumulation of other substances such as medium-chain fatty acids and certain peptides/proteins [ 9 , 10 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This indicated that, although yeast died early, the ethanol likely inhibited the LAB, supported by the different ethanol levels and different LAB counts in co- and sequential fermentation. The results agreed with a previous study [ 10 ], where the highest cell population of LAB in mixed inoculation was also similar to that of LAB mono-inoculation. In addition, the decline of LAB may also be due to the lack of nutrients or the accumulation of other substances such as medium-chain fatty acids and certain peptides/proteins [ 9 , 10 ].…”
Section: Resultssupporting
confidence: 92%
“…The results agreed with a previous study [ 10 ], where the highest cell population of LAB in mixed inoculation was also similar to that of LAB mono-inoculation. In addition, the decline of LAB may also be due to the lack of nutrients or the accumulation of other substances such as medium-chain fatty acids and certain peptides/proteins [ 9 , 10 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In other ciders the obtained isobutanol values were similar to those obtained by Loira et al [ 60 ]. This shows that not only the yeast strain used has a significant impact on the concentration of volatile compounds, but also that the addition of minerals contributed to obtaining a similar value of higher alcohols in the analyzed ciders compared to the results obtained by other researchers [ 61 ]. Magnesium ions play a fundamental role in the growth and metabolism of yeast cells.…”
Section: Resultssupporting
confidence: 70%
“…In recent years, researchers worldwide have been paying particular attention to T. delbrueckii exploitation to improve wines organoleptic final profile and quality. As referred above, its physiological and metabolic properties revealed positive effects in wines characteristics towards acids and sugar consumption, but also an enhancement of the aroma complexity through the production of important metabolites [ 2 , 3 , 4 , 23 , 56 , 57 , 58 , 59 ]. During wine fermentation, higher alcohols (also termed fused alcohols) and esters contribute 30 to 80% to the aroma profiles of wine, being the two most relevant groups of metabolites [ 59 ].…”
Section: Biotechnological Importance Of T Delbrueckiimentioning
confidence: 99%